Development of high-resolution dynamic dust source function - A case study with a strong dust storm in a regional model. (June 2017) - Kim, Dongchul; Chin, Mian; Kemp, Eric M.; Tao, Zhining; Peters-Lidard, Christa D.; Ginoux, Paul
Abstract: A high-resolution dynamic dust source has been developed in the NASA Unified-Weather Research and Forecasting (NU-WRF) model to improve the existing coarse static dust source. In the new dust source map, topographic depression is in 1-km resolution and surface bareness is derived using the Normalized Difference Vegetation Index (NDVI) data from Moderate Resolution Imaging Spectroradiometer (MODIS). The new dust source better resolves the complex topographic distribution over the Western United States where its magnitude is higher than the existing, coarser resolution static source. A case study is conducted with an extreme dust storm that occurred in Phoenix, Arizona in 02–03 UTC July 6, 2011. The NU-WRF model with the new high-resolution dynamic dust source is able to successfully capture the dust storm, which was not achieved with the old source identification. However the case study also reveals several challenges in reproducing the time evolution of the short-lived, extreme dust storm events. Highlights: A high-resolution dynamic dust source has been developed. New dust source better resolves the complex topographic distribution. A case study is successfully conducted with a strong dust storm in NU-WRF.